FRONTIR-ISASI DAN DE-FRONTIR-ISASI SEBAGAI KERANGKA UNTUK STUDI MARJINALITAS: STUDI KASUS LINDU DI SULAWESI TENGAH - Acciaioli, Gregory Lawrence; Nasrum, Muhammad (Jurnal Masyarakat dan Budaya, 2020)
AbstractDrawing on past and recent literature using the concept frontier, this paper presents a case study of processes of frontierisation and defrontierisation in the Lindu plain of Central Sulawesi. After establishing the rationale for a more processual framework to analyse frontiers, it traces the history of the Lindu plain along the four dimensions of frontierisation related to control, extraction, settlement and conservation from the precolonial era to the contemporary post-Reformasi period. Using this Lindu case study, it seeks to reconceptualise such notions as the closing of frontiers by drawing attention away from certain demographic and economic thresholds of occupation and by emphasising instead the exercise of agency on the parts of marginalised local peoples in frontier regions, allowing them to reverse the asymmetric relations of the (dominant) occupiers and (subordinated) occupied that have constituted frontiers. This is illustrated by the changing position of the Indigenous Lindu people as subordinated first by colonial incursions and then in the immediate postcolonial period through domination by entrepreneurial Bugis migrants whose own position was buttressed by alliances with governmental agencies to the contemporary reassertion of their control over their own territory through alliances with both the Indonesian Indigenous people?s movement and with transnational conservation.Keywords: Frontier, Frontierisation, Defrontierisation, Marginality, Marginal Societies, Lindu Bugis, Central Sulawesi  AbstrakBersandar kepada naskah lama dan mutakhir yang menggunakan konsep frontir, makalah ini menyajikan studi kasus proses frontir-isasi dan de-frontir-isasi di dataran Lindu, Sulawesi Tengah. Sesudah memberikan alasan untuk kerangka yang memusatkan proses, artikel ini menggambarkan sejarah Lindu melalui empat dimensi frontir-isasi ? kendali, ekstraksi, pemukiman dan konservasi ? dari zaman prakolonial sampai era Pasca-Reformasi. Studi kasus ini digunakan untuk memikirkan kembali gagasan seperti penutupan frontir; daripada indicator demografis dan ekonomis, daya tindak (agensi) dari masayakarat lokal yang didominasi/dipinggirkan dalam usaha membalikkan relasi-kuasa menjadi kriterium yang dipusatkan sebagai unsur utama penutupan frontir atau de-frontir-isasi. Proses penggulingan ini dicontohkan oleh perubahan posisi To Lindu sebagai orang asli di wilayah ini. Mulai dari keadaan dipinggirkan di masa kolonial sampai ke era paska-kolonial waktu mereka didominasi oleh migran Bugis yang memperkuat usaha kewiraswastaannya dengan menggunakan alasan pembangunan dan aliansi dengan instansi permerintah, akhirnya di era Reformasi dan Pasca-Reformasi To Lindu sempat menarik kembali penguasaan atas wilayahnya melalui aliansi dengan gerakan masyarakat adat dan organisasi konservasi.Kata kunci: Frontir, Frontir-isasi, Defrontir-isasi, Marjinalitas, Masyarakat Pinggiran, Lindu, Bugis, Sulawesi Tengah